Sub-budaya Mat Rempit dan perubahan sosiobudaya - Muhamad Fuad Abdul Karim,; Rokiah Ismail,; Mohamad Fauzi Sukimi, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2009)
Illegal motorcycle racing is an informal sport of Malaysian urban youths which is increasingly perceived by the Malaysian society as a real social nuisance. The racers are nicknamed Mat Rempit in Malay. This paper takes the view that, in general, the Mat Rempit activities may be related to some sociocultural impacts of the contemporary social change process in the Malaysian society. It analyses findings of a study conducted in a Kuala Lumpur social setting, the focal points of which were the activities and the specifics of the Mat Rempit sub-culture. These included the Mat Rempit spoken and conversation language, and the norms and values to which members of the Mat Rempit subscribed. A total of 45 Kuala Lumpur’s Mat Rempit, aged between 17 and 26, became the respondents of the study which employed in-depth interview and observation techniques. The study found that the Mat Rempit groups not only engaged in illegal racing but also other activities considered negative by the general public. The Mat Rempit subculture evolved and perpetuated through group learning processes, and was characterised by counterculture elements which were the sociocultural outcomes of the social transformation processes undergone by certain quarters of the Malaysian youth population. In conclusión, the Mat Rempit sub-culture finds expressions in values such as freedom, identity, autonomy, pleasure, appearence and creativity